Diagnosis of Mycoplasma gallisepticum from a Broiler Breeder Flock: Comparison of Three Diagnostics Methods - Evans, J.D.; Thornton, D.L.; Branton, S.L. (International Journal of Poultry Science, 2009)
NPIP-mandated serological screening of a multiplier breeder flock detected possible Mycoplasma gallisepticum (MG) exposure. The flock was quarantined and further samples including blood and choanal swabs were collected and sent to a research facility for independent testing and confirmation. Subsequent analyses included diagnosis by Serum Plate Agglutination (SPA), MG-specific Polymerase Chain Reaction (PCR) and culture identification. Results of the various diagnostic tests were compared. The findings of the various diagnostic tests were in agreement and confirmed MG infection of the breeder flock. Time requirements of the various diagnostic procedures were recorded and were 1 h, 27 h and 30 days for SPA, MG-specific PCR and culture identification, respectively. The results affirm the validity of the diagnostic procedures and emphasize the importance of timely screening and diagnostic procedures for control of MG.